The Strategic Role of Social Media as a Marketing Communication Tool to Enhance the Competitiveness and Sales of MSMEs - Sutrisno, Sutrisno; Yani, Ahmad; Diawati, Prety (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Social media offers high accessibility and broad reach. With relatively low costs, MSMEs can reach a larger and more diverse audience compared to traditional media. This research aims to understand how social media can be strategically utilized by MSMEs as a marketing communication tool to enhance their competitiveness and sales. This research is a literature review study with a qualitative approach. The data sources used in this study were obtained from scholarly articles accessed through Google Scholar from 2014-2024. The study results show that social media has proven to be an essential element in marketing strategies for MSMEs. By effectively utilizing social media, MSMEs can build a strong online presence, engage in two-way dialogues with customers, maintain close relationships with existing customers, reach global markets at affordable costs, and better measure their marketing performance. Thus, social media not only becomes a communication tool but also a key to success for MSMEs in this digital era.